Random Amplified Polymorphic DNA Analysis of Four Breeds of Sheep in Malaysia - Vijaya Kumar, (1999)

(untitled)
The genetic variability and population structure of four populations of sheep breeds namely, Santa Ines, Barbados Blackbelly, Malin and the Dorset-Malin cross, was investigated using the Random Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR). Eight 10-meroligonucleotide primers of arbitrary sequence (OPD-03, OPD-09, OPD-11, OPD-12, BRL-02, BRL-03, BRL-05, BRL-06) were used to amplify discrete regions of the sheep genome from 30 individuals per breed. The amplified product was electrophoresed using agarose gels to reveal banding patterns that could differentiate between individuals. These primers revealed a total of 65 DNA markers with a range in size of 228-1,871 bp. Of these markers, 38 or 58.5% were polymorphic while 27 or 42.5% were monomorphic. Primer OPD-09 amplified seven bands but all bands were 100% monomorphic in the four breeds. Two markers, BRL03.1 and BRL03.5 were found to be common and exclusive for the wool sheep breeds. Genetic distance was calculated using both the Dice's and Jaccard's similarity indices. High genetic values were seen within the Santa Ines breed (Dice: 0.0930; Jaccard: 0.1682) while the least variable population was the Dorset-Malin cross (Dice: 0.00693; Jaccard: 0.1280). Genetic distance values for Barbados Blackbelly and Malin was calculated as 0.0748 (Dice)/O.1378 (Jaccard) and 0.0813 (Dice)/O.0813 (Jaccard) respectively. The neighbour-joining and the UPGMA trees based on the Dice's and Jaccard's similarity indices showed little or no consensus on the clustering of the individuals in each population. Genetic distance between populations ranged from 0.1040 to 0.1357 based on the Dice's algorithm while the distance based on the Jaccard's algorithm ranged from 0.1875 to 0.2381. Greatest similarity was observed between Santa Ines and Barbados Blackbelly breeds (Dice: 89.6%; Jaccard: 81.2%) while the Santa Ines and the Dorset-Malin cross were the least similar (Dice: 86.4%; Jaccard: 76.2%). The neighbour-joining and UPGMA analysis showed the Santa Ines and Barbados Blackbelly to be closely linked, while the hair sheep breeds were closely related to the Malin. The Dorset-Malin cross was genetically furthest away from the rest of the breeds. Consensus tree produced after 100 bootstrapping show a confidence level of 78% between the Santa Ines and Barbados Blackbelly branch and a 61% confidence level between the hair sheep breeds and the Malin. Total number of phenotypes per primer ranged from 1 (OPD-09) to 62 (BRL-06). The Santa Ines population had a total of 61 phenotypes, which was the largest, followed by Barbados Blackbelly (56), Malin (54) and Dorset-Malin (43). All primers (except OPD-09) had phenotypes common either to the hair sheep or wool sheep breeds. The analysis of molecular variance showed that four out of the seven polymorphic primers (OPD-11, OPD-12, BRL-03, and BRL-06) were able to detect variance among fleece type, among populations and among individuals in a population. Primers OPD-03 and BRL-02 were unable to detect significant variance among the hair and wool breeds, while primer BRL-05 was unable to detect significant variance among the populations. Primer OPD-11 detected the highest variance among individuals (91.08%) while primer BRL-02 detected the lowest variance among individuals (8.46%). Overall data showed 74% variance among individuals within population, 20% variance among populations and 4% variance among fleece types. The genetic variability and structure of the four populations of sheep were identified through the RAPD-PCR assay. Such information is necessary in order to devise breeding or crossbreeding programs for the development of the sheep industry.